(untitled) (Heritage, 2022)
Most of the research on the translation equivalents of the direct and indirect speech were dealing with translations from English to Serbian language. In this paper, we investigate whether structural and/or stylistic movements occur when the free direct and free indirect speech (and their subtypes) are translated from Serbian language to English language. Novel De bello civili by Svetislav Basara is used as a research corpus. Аlmost all types of direct and indirect speech are present in the novel. Events in the novel take place very quickly, since the plot of the novel takes place in one day, reminding us how substantial the events of a single day can be. The events in the reality of fiction and events in the inner world of protagonists are mixed here, and hence the dominance of free direct speech. The research led to conclusion that forms in free indirect speech in English and Serbian language share most of the features, except for the sequence of tenses that is inherent in English and not in Serbian language. Since free direct speech does not include the shift of tenses, the examples of this type of reported speech are almost identical in both languages. Given that the narrator of the novel is at the same time the leading protagonist whose words are communicated, there is the omission of prenominal focalization, and there are cases when it is difficult to distinguish the free direct speech from free indirect speech. This imply the omission of author’s speech and orthographic markers, which may impose a problem during translation. From the given examples, it can be seen that in some cases the translator was not guided by the Serbian language, in terms of following and communicating the reported speech. Although the free indirect speech is more flexible category in the Serbian language (Каравесовић 2010), when translating into English there is often a problem of transferring all stylistic features. Following the rule of the sequence of tenses that is inherent in the English language, but not in Serbian, the translator diminishes the actuality achieved by the use of the free indirect speech in the original. Furthermore, sometimes it is very difficult to distinguish between the free direct and free indirect speech in the Serbian language; these two types of reported speech cannot be equalized in the English translation, and usually the indirect speech with subtypes is used as translation equivalent.